Environmental consultants, knowledge brokering and policy-making: a case study. (2017) - Sardo, Ana Margarida; Weitkamp, Emma
This small-scale exploratory study examined the role of environmental consultants in the policy-making process using one European country (Portugal) as a case study. The study focused particularly on the role of environmental consultants as knowledge brokers, providing scientific expertise to national and local government policy-makers. The research question and other topics were explored through in depth interviews and an online questionnaire. The data indicate that in Portugal environmental consultants act as knowledge brokers, providing policy-makers with access to scientific information and encouraging its use; this information feeds into the policy process at the formulation, implementation, assessment and review stages. They also play other roles such as acting as financial, legal and technical advisors.